PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS DISCOVERY LEARNING PADA MATA PELAJARAN BIOLOGI - Three Putri Nirmala Bu'ulolo; Toroziduhu Waruwu; Novelina Andriani Zega; Hardikupatu Gulo (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The rapid development of educational technology demands innovative learning media that can enhance student engagement and learning outcomes. However, Biology instruction at SMA Negeri 1 Susua is still dominated by lecture-based methods and textbooks, resulting in low student participation and learning outcomes that have not reached the Minimum Mastery Criteria (KKM). This condition indicates a gap between the demands of 21st-century student-centered learning and the current teacher-centered instructional practices, highlighting the need for media that facilitate independent concept discovery. This study aimed to develop a Discovery Learning–based instructional video for Grade XI Biology and to evaluate its feasibility, practicality, and effectiveness. This study employed a Research and Development (R&D) approach using the ADDIE model (analysis, design, development, implementation, and evaluation). The research subjects were 26 students of class XI-MIPA. The instruments included expert validation sheets, student response questionnaires, and learning outcome tests, which were analyzed descriptively using a Likert scale and percentage techniques. The results showed that the developed video achieved a feasibility level of 82.29% (feasible) and a practicality level of 88.53% (very practical). The average learning outcome score reached 81.92 with a classical mastery level of 84.62%. Therefore, the Discovery Learning–based instructional video developed in this study is considered feasible, practical, and effective for Biology learning. ABSTRAK Perkembangan teknologi pendidikan menuntut inovasi media pembelajaran yang mampu meningkatkan keterlibatan dan hasil belajar peserta didik. Namun, pembelajaran Biologi di SMA Negeri 1 Susua masih didominasi metode ceramah dan buku paket sehingga partisipasi siswa rendah dan hasil belajar belum mencapai KKM. Kondisi ini menunjukkan kesenjangan antara tuntutan pembelajaran abad ke-21 yang berpusat pada siswa dengan praktik pembelajaran yang masih berpusat pada guru, sehingga diperlukan media yang mendorong penemuan konsep secara mandiri. Penelitian ini bertujuan mengembangkan video pembelajaran berbasis Discovery Learning pada mata pelajaran Biologi kelas XI serta menilai kelayakan, kepraktisan, dan efektivitasnya. Penelitian ini merupakan Research and Development (R&D) dengan model ADDIE (analisis, desain, pengembangan, implementasi, evaluasi). Subjek penelitian adalah 26 peserta didik kelas XI-MIPA. Instrumen meliputi lembar validasi ahli, angket respon siswa, dan tes hasil belajar yang dianalisis secara deskriptif menggunakan skala Likert dan persentase. Hasil menunjukkan tingkat kelayakan sebesar 82,29% (layak) dan uji kepraktisan sebesar 88,53% (sangat praktis). Nilai rata-rata hasil belajar mencapai 81,92 dengan ketuntasan klasikal 84,62%. Dengan demikian, video pembelajaran berbasis Discovery Learning yang dikembangkan dinyatakan layak, praktis, dan efektif untuk pembelajaran Biologi.